2020
DOI: 10.3748/wjg.v26.i38.5896
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus and mycophenolate mofetil as second-line treatment in autoimmune hepatitis: Is the evidence of sufficient quality to develop recommendations?

Abstract: BACKGROUND The standard management of autoimmune hepatitis (AIH) is based on corticosteroids, alone or in combination with azathioprine. Second-line treatments are needed for patients who have refractory disease. However, high-quality data on the alternative management of AIH are scarce. AIM To evaluate the efficacy and safety of tacrolimus and mycophenolate mofetil (MMF) and the quality of evidence by using the Grading of Recommendations Assessment, Development and Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Although several systematic reviews were published on CNIs in the treatment of adult AIH, interpretation of the published data is hampered by heterogeneity of the outcome measures. [16][17][18][19][20][21] In this systematic review, we addressed that problem by redefining the treatment outcomes in the articles according to established definitions. [16][17][18][19][20] In studies describing the use of MMF in the treatment of AIH, the reason for starting MMF (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although several systematic reviews were published on CNIs in the treatment of adult AIH, interpretation of the published data is hampered by heterogeneity of the outcome measures. [16][17][18][19][20][21] In this systematic review, we addressed that problem by redefining the treatment outcomes in the articles according to established definitions. [16][17][18][19][20] In studies describing the use of MMF in the treatment of AIH, the reason for starting MMF (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two previously published reviews reported pooled remission rates of 41% and 32% on MMF. 21,48 Compared with MMF, CNIs seem more effective in that group, but there is no available head-to-head comparison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations